Relationship between Depression and Distress with Age and Gender in Patients with Type 2 Diabetes - Carlos, Figueroa López; Bertha, Ramos del Río; Santiago, Rincón Salazar; Suvalsky Zarkin, Elias (Advances in Social Sciences Research Journal, 2025)
The objective of this study was to determine the relationship between depression and distress with the age and gender of patients with type 2 diabetes. 237 patients. with medical diagnosis of type 2 diabetes for at least one year; age between 18 and 70 years participated in the study. Distress was measured with “The Problem Areas in Diabetes (PAID) Scale”, and depression with “The Patient Health Questionnaire (PHQ-9)”. Negative correlations were found between age and depression (r = -0.203, p < 0.01) and distress (r = -0.34, p < 0.001). And a positive relationship was also observed between depression and distress (r = 0.65, p < 0.001). Also significant differences were found, with women presenting higher scores in both depression (PHQ) (t = -3.466, p < 0.001) and distress (PAID) (t = -4.504, p < 0.001). The factors of depression, distress, gender, and age are crucial for understanding the entirety of the patient’s experience with diabetes. To improve disease control and quality of life, it is essential to adopt an integrated approach that respects the diversity of patients' experiences and provides them with appropriate support.